Heat exposure and occupational injuries: Review of the literature and implications - Spector, June T. (Curr Environ Health Rep, 2019)
PURPOSE OF REVIEW: The burden of heat-related adverse occupational health effects, as well as traumatic injuries, is already substantial. Projected increases in mean temperatures and extreme events may increase the risk of adverse heat health effects and enhance disparities among exposed workers. This article reviews the emerging literature on the relationship between heat exposure and occupational traumatic injuries and discusses implications of this work. RECENT FINDINGS: A recent meta-analysis of three case-crossover and five time-series studies in industrialized settings reported an association of increasing occupational injuries with increasing heat exposure, with increased effect estimates for male gender and age less than 25 years, although heterogeneity in exposure metrics and sources of bias were demonstrated to varying degrees across studies. A subsequent case-crossover study in outdoor construction workers reported a 0.5% increase in the odds of traumatic injuries per one °C increase in maximum daily humidex (odds ratio 1.005 [95% CI 1.003–1.007]). While some studies have demonstrated reversed u-shaped associations between heat exposure and occupational injuries, different risk profiles have been reported in different industries and settings. SUMMARY: Studies conducted primarily in industrialized settings suggest an increased risk of traumatic injury with increasing heat exposure, though the exact mechanisms of heat exposure’s effects on traumatic injuries are still under investigation. The effectiveness of heat-related injury prevention approaches has not yet been established. To enhance the effectiveness of prevention efforts, prioritization of approaches should not only take into account the hierarchy of controls, social-ecological models, community and stakeholder participation, and tailoring of approaches to specific local work settings, but also methods that reduce local and global disparities and better address the source of heat exposure, including conservation informed land-use planning, built environment, and prevention through design approaches. Participation of occupational health experts in transdisciplinary development and integration of these approaches is needed.